The Effect Of Brand Identity, Brand Image, Brand Integrity And Brand Interaction On Customer Satisfaction And Purchase Intention (Case Study On Iphone Smartphone Fans In Indonesia) - Taufik, fiqri; Hartono, Arif (Cita konsultindo, 2025)
This study aims to examine the influence of brand identity, brand image, brand integrity, and brand interaction on consumer satisfaction and consumer purchasing interest. This study uses the iPhone smartphone as the object of research, which is one of Apple's products, using a quantitative approach. The data collection method was by distributing online questionnaires to 280 respondents, but there were 200 respondents who met the research criteria. The sampling technique used a non-probability sampling technique using the purposive sampling method, then the data was processed statistically using Structural Equation Modeling (SEM) using Partial Least Square (PLS). The results of this study indicate that: 1) Brand identity has a positive and significant effect on consumer satisfaction, 2) Brand image, brand integrity, and brand interaction have a positive effect on customer satisfaction, 3) Brand identity, brand image, brand integrity and brand interaction have a positive effect on purchase intention, and 4) customer satisfaction has a positive effect on purchase intention.